2012
DOI: 10.1248/bpb.35.889
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Evaluation of Nasal Mucociliary Clearance Using Excised Rat Nasal Septum

Abstract: Mucus on the nasal mucosa is translocated to the pharynx by ciliary beating, which is an important nonspecific defense mechanism called mucociliary clearance (MC). MC is one of the important factors determining the rate and extent of drug absorption after nasal application. The purpose of this study is to evaluate MC using rat nasal septum under physiological condition in an in vitro system. The nasal septum was excised from rats anesthetized with urethane and the movement of fluorescent microspheres (FMS) app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…7), suggesting that CFZ does not affect ciliary function at these concentrations. No effect of CFZ on MC was also confirmed by following the method reported previously 3) (Table 1). Relationship between CBF and MC Finally, the relationship between CBF and MC was investigated utilizing our previously reported results for MC.…”
Section: Determination Of Cbfsupporting
confidence: 74%
See 3 more Smart Citations
“…7), suggesting that CFZ does not affect ciliary function at these concentrations. No effect of CFZ on MC was also confirmed by following the method reported previously 3) (Table 1). Relationship between CBF and MC Finally, the relationship between CBF and MC was investigated utilizing our previously reported results for MC.…”
Section: Determination Of Cbfsupporting
confidence: 74%
“…16) Our present MC results are cited from our previous study. 3) study also showed that ATRP decreased CBF to 78 and 82% of the control at concentrations of 1 µm and 100 µm, respectively (Fig. 6).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Fluorescent polyethylene microspheres may be an alternative to carbon in studies of mucociliary clearance. Polyethylene microspheres have been used for the demonstration of mucociliary activity in the respiratory epithelium of other species (14,15,17). Advantages of fluorescent microspheres are that they are non-toxic, inert, and highly visible.…”
Section: Polyethylene Microspheresmentioning
confidence: 99%